2010
DOI: 10.1103/physrevb.82.054104
|View full text |Cite
|
Sign up to set email alerts
|

Melting of Lennard-Jones rare-gas clusters doped with a single impurity atom

Abstract: Single impurity effect on the melting process of magic number Lennard-Jones, rare gas, clusters of up to 309 atoms is studied on the basis of Parallel Tempering Monte Carlo simulations in the canonical ensemble. A decrease on the melting temperature range is prevalent, although such effect is dependent on the size of the impurity atom relative to the cluster size. Additionally, the difference between the atomic sizes of the impurity and the main component of the cluster should be considered. We demonstrate tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…6a exhibits additional low-temperature peaks that also change with σ r . Analogous C V features have been reported previously 19 and attributed to dopant delocalisation prior to melting. Here we also interpret these features as indicators of non-degenerate permutational isomerisation (see below), and the fact that they change systematically with σ r indicates potentially tunable behaviour.…”
Section: Inset)supporting
confidence: 84%
See 2 more Smart Citations
“…6a exhibits additional low-temperature peaks that also change with σ r . Analogous C V features have been reported previously 19 and attributed to dopant delocalisation prior to melting. Here we also interpret these features as indicators of non-degenerate permutational isomerisation (see below), and the fact that they change systematically with σ r indicates potentially tunable behaviour.…”
Section: Inset)supporting
confidence: 84%
“…This result is consistent with previous experiments 10,11 and calculations. [12][13][14][15][16]18,19 More importantly, we have shown that a given solid-solid transition supports only a limited range of atom-size mismatch, and exceeding the system-specific limits will destroy the transition. Hence, a transition temperature can be tuned only by impurities with mismatch magnitude below a certain tolerance, which is generally larger for surface (as opposed to interior) impurities.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The distortion of the system lattice leads to the change in energetics as well as entropy of the cluster. The reduction of the melting temperature of magic Lennard-Jones clusters due to a single impurity has also been observed …”
Section: Introductionmentioning
confidence: 87%
“…14 In addition, single atom impurities in pure component clusters can also cause doping effects, such as the change of melting temperature or the solid-solid transition at low temperatures. 15,16 Experimental results show that the addition of a carbon atom to small-size Ni clusters can change the thermodynamic properties of these Ni clusters. And the existence of carbon impurities can significantly change the migration and diffusion of atoms in the Ni clusters at temperatures close to the melting point.…”
Section: Introductionmentioning
confidence: 99%